The Britishness of 'British Video Games'. Issue 2 (23rd February 2020) - Webber, Nick
Abstract: British Government policy has much to say about video games, through production support, regulation and recognition (or lack of it) of their cultural nature, with games defined and promoted as part of the creative industries in a manner which owes much to film policy. Yet, the drive to promote both the games industry and games culture, and the inconsistent usage of terms like culture and creativity, produces tensions between different elements of 'Britishness', expressed and experienced not only through policy, but also through the creation and consumption of games. In considering the specificity of games' contribution to British identity, therefore, we must understand how different elements of cultural policy interact with the interests of audiences and creators to define 'British games' – games which have the quality of being, or being seen to be, British. Such games might be expected not only to represent British culture within a global marketplace, and to project soft power, but also to address the British nation in some manner. This diversity, of global and local, of present-mindedness and nostalgia, suggests that British games articulate a complex and plural sense of national (cultural) identity.